2010
DOI: 10.1007/s10549-010-0745-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening for genomic rearrangements in BRCA1 and BRCA2 genes in Czech high-risk breast/ovarian cancer patients: high proportion of population specific alterations in BRCA1 gene

Abstract: Large genomic rearrangements (LGR) represent substantial proportion of pathogenic mutations in the BRCA1 gene, whereas the frequency of rearrangements in the BRCA2 gene is low in many populations. We screened for LGRs in BRCA1 and BRCA2 genes by multiplex ligation-dependent probe amplification (MLPA) in 521 unrelated patients negative for BRCA1/2 point mutations selected from 655 Czech high-risk breast and/or ovarian cancer patients. Besides long range PCR, a chromosome 17-specific oligonucleotide-based array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
4
23
1
Order By: Relevance
“…For instance, LGRs account for 2% of all BRCA2 and 12.5% of all BRCA1 disease-causing mutations detected in a Danish cohort [4]. Similar findings are observed in Australian (2.3% vs. 14.9%), Malaysian (4% vs. 8%), Italian (0% vs. 10.5%), Czech Republic (0% vs. 12.3%), or USA (6% vs. 22%) cohorts [5][6][7][8][9]. In Spain, previous studies detected BRCA2 LGRs in 1.5%, and BRCA1 LGRs in 2.8% of the families analyzed [10,11].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…For instance, LGRs account for 2% of all BRCA2 and 12.5% of all BRCA1 disease-causing mutations detected in a Danish cohort [4]. Similar findings are observed in Australian (2.3% vs. 14.9%), Malaysian (4% vs. 8%), Italian (0% vs. 10.5%), Czech Republic (0% vs. 12.3%), or USA (6% vs. 22%) cohorts [5][6][7][8][9]. In Spain, previous studies detected BRCA2 LGRs in 1.5%, and BRCA1 LGRs in 2.8% of the families analyzed [10,11].…”
Section: Introductionsupporting
confidence: 62%
“…Overall, we have detected BRCA2 LGRs in 7 out of 836 HBOC families analyzed, supporting a low proportion of these alterations in our population. Indeed, a low proportion (ranging from 0 to 2.5%) has been reported in most populations analyzed [3,[5][6][7][8][9]30]. Some authors have reported male breast cancer patients in most families harboring BRCA2 LGRs, thus suggesting a strong association with this malignancy [4,5,21].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic rearrangements accounted for 18.2% (4/22) of the BRCA1 mutations detected in these patients. This rate is somewhat higher than those previously recorded in other populations such as in Spain (8.2%) [19], Germany (9.6%) [20], France (12.0%) [5], Czech Republic (12.3%) [21] and Denmark (12.5%) [22], but is lower than that recorded in the Netherlands (27.3%) [13]. Our reported percentage is in agreement with the results of Agata et al in Italy, who reported about 19% of LGRs in a large cohort of breast and breast/ovarian cancer families without BRCA1 and BRCA2 point mutations detectable by conventional scanning methods [14].…”
Section: Discussioncontrasting
confidence: 60%
“…34 The majority of these elements lost their transposition ability a long time ago, although some of them, in particular, LINE-1 and Alu, have been shown to maintain this capacity, thus contributing to recent evolutionary history of the primate genomes 35 and also to the genomic instability found to be involved in cancer and several genetic disorders. 36 Similar to what happens with the BRCA1 gene, often known to suffer Alu-mediated deletions, 37,38 analysis of SPG11 also shows a high density of interspersed repeats, namely Alu elements, which together with the large size of this gene (~101 kb) favors the occurrence of various rearrangements. In addition, and similar to what seems to be happening with the SPG11 deletions, the Alu-mediated BRCA1 rearrangements arise from nonallelic homologous recombination.…”
Section: Evolutionary Conservation Of Alus Involved In Human Spg11 Dementioning
confidence: 82%